Políticas curriculares e educação antirracista: transgressões possíveis na educação básica - Fagundes, Fabiane Soares dos Santos (2023)
This work, from the Professional Master's Course, from the Postgraduate Program in Public Policies in Educational Management of the Basic and Higher Education Policies and Management Research Line, addresses the topic of curriculum policies and anti-racist education. As a general objective, it prioritized investigating curricular policies that promote changes in pedagogical practices based on an anti-racist curriculum. The specific objectives prioritized identifying anti-racist curricular policies aimed at the public school curriculum; understand the theoretical perspectives constructed regarding anti-racist education; analyze teacher training materials on anti-racist curriculum policies for Basic Education teachers; reflect on transgressive pedagogical proposals in the construction of anti-racist education. The theoretical framework is organized based on authors such as Hooks (2017), Kilomba (2019), Ribeiro (2019), Sacristán (2000), among others who contribute to the improvement and reflection on the research topic. To obtain data, it was based on a qualitative research approach, using bibliographic research techniques and data analysis was based on content analysis. What can be considered is that the result obtained after analysis shows that the curricular policies provide the basis for the different themes to be worked on, but it is clear that when they are combined with anti-racist issues, the themes are a little vague, as It is believed that one cannot just recognize that privilege exists and not actually have an anti-racist stance. Black people need to transgress the barriers regarding their attitude towards society. The product resulting from the research was an (in)formative guide, whose purpose and contributions are to help teachers find information in a quick and organized manner, regarding Public and Educational Policies, Curricular Policies based on the anti-racist curriculum. It is hoped that this research can contribute to improving teachers' knowledge to develop educational practice in a diverse and anti-racist way.